Campylobacter enteritis presenting as an acute abdomen. Issue 653 (March 1980) - Hay, D. J.; Ganguli, L. A.
Abstract : A case is reported of a young patient with Campylobacter enteritis who underwent first appendicectomy and then a laparotomy because of the severity of the pain and the marked abdominal signs.